PEMBELAJARAN THINK-TALK-WRITE DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN SOAL GEOMETRI - Prayitno, Anton (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
Studentsâ poor ability in completing geometry questions is one of the crucial problems in mathematics education. In this mixed method research, Think-Talk-Write cooperative learning was used to enhance seventh-grade studentsâ ability in completing geometry questions. Samples were 35 seventh grade students in one of junior high school in East Java. Instruments were studentsâ worksheets (LKS), written test, as well as observation sheets. Think-Talk-Write learning was conducted in two learning sessions. Results showed that Think-Talk-Write learning increased studentsâ ability in completing geometry questions, both in completing questions in the LKS and in the written test. Steps in Think-Talk-Write learning help the students to reflect, organize, and improve their understanding so that they are able to answer the given geometry questions better. In addition to the contribution of each step in Think-Talk-Write learning itself, teacher also contributed to studentsâ improved ability in completing geometry questions, especially in terms of detecting and guiding the studentsâ to overcome difficulties in completing geometry questions.